Undergraduate Nursing Students’ Experiences Of Their Clinical Practice - Lim, Lily (University Malaysia Sarawak, UNIMAS, 2013)
This qualitative research explored the nursing students’ perception of their clinical experiences on their posting at the Malaysian health care settings. Students’ expectation, feelings, challenging experiences related to work culture, knowledge and skills in patient care, teaching learning supports, people interpersonal relationship, students’ role and their coping mechanism in nursing were explored. The data were collected from interviews using purposive sampling. The participants were undergraduate nursing students who had their clinical postings at the hospitals and clinics in Malaysia. Data were analysed and themes emerged to illustrate the students’ clinical experiences.The findings were categorized into three major themes that included: 1) “Gaining insight into the hospital setting”; 2) “Challenges”; 3) “Coping mechanism”. These themes were then further subcategorized for easy understanding. For example, the subthemes for “Gaining insight into the hospital setting” included: the reality of the ward; doing ward routine; and working with other categories of health staff. The study also identified challenging clinical experiences that students faced. Challenges included being labelled as “degree nursing students”, theory-practice gap, problems related to insufficient clinical practices and supervision. The students were able to use different coping mechanism such as internal and external motivation which led to gain confidence as they progressed in their learning. This study proposed practical strategies to empower students in clinical learning and increase their self-esteem and confidence. In order to improve quality of students’ clinical education, adequate and effective work collaboration between nursing education and health care services are recommended. Future research should look into other aspects of students’ clinical experiences such as students’ teaching-learning support system and patients’ perception of the care services provided by the students.